ANALISIS RASCH DALAM UTRECHT WORK ENGAGEMENT SCALE-9 (UWES-9) VERSI BAHASA INDONESIA - Kristiana, Ika Febrian; Fajrianthi, Fajrianthi; Purwono, Urip (Jurnal Psikologi, 2018)
Using a scale in different cultural contexts requires an adaptation process for the sake of fair comparison between obtained scores. The 9-item version of Utrecht Work Engagement Scale (UWES-9) has been adapted in various countries but Indonesia. This study aimed to make a scale adaptation of the UWES-9 in Indonesia. A hundred teachers of inclusive schools in Solo, Semarang, Surabaya, and Malang were involved as participants. Data were collected both online and paper-based. Confirmatory Factor Analysis (CFA) and Rasch test were used to analyze the data. Result showed that the UWES-9 had high values of: overall person and item interaction (Î±= .85); person reliability (= .71); and item reliability (= .95). The person measure value (=1.65 logit) and separation value 1.57 indicated two respondent groups based on the degree of work engagement. The item 5 had outfit value MNSQ > 14, meaning that it was unfit. Some items were found biased toward teaching duration in inclusive school. Internal structure analysis using CFA showed that UWES-9 is a unidimensional instrument with established goodness of fit value (RMSEA = .049; CFI, NFI, & GFI > .95). To conclude, UWES-9 has adequate psychometric properties, so it can be used for research or assessment.